2015
DOI: 10.1016/j.bpj.2015.03.039
|View full text |Cite
|
Sign up to set email alerts
|

CNS Cell Distribution and Axon Orientation Determine Local Spinal Cord Mechanical Properties

Abstract: Mechanical signaling plays an important role in cell physiology and pathology. Many cell types, including neurons and glial cells, respond to the mechanical properties of their environment. Yet, for spinal cord tissue, data on tissue stiffness are sparse. To investigate the regional and direction-dependent mechanical properties of spinal cord tissue at a spatial resolution relevant to individual cells, we conducted atomic force microscopy (AFM) indentation and tensile measurements on acutely isolated mouse spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
159
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(175 citation statements)
references
References 57 publications
13
159
3
Order By: Relevance
“…For example, grey matter regions in the cerebellum, consisting mainly of cell bodies, tend to be stiffer (Young's modulus measured with AFM, E ≈ 450 Pa) than white matter regions (E ≈ 300 Pa), which essentially contain many axonal tracts 60 . A similar result has been reported for the rat spinal cord measured with AFM, further demonstrating the greater anisotropy of white matter 53 . Even on a larger scale, this result seems to hold 61 .…”
Section: Tissue Considerationssupporting
confidence: 73%
See 2 more Smart Citations
“…For example, grey matter regions in the cerebellum, consisting mainly of cell bodies, tend to be stiffer (Young's modulus measured with AFM, E ≈ 450 Pa) than white matter regions (E ≈ 300 Pa), which essentially contain many axonal tracts 60 . A similar result has been reported for the rat spinal cord measured with AFM, further demonstrating the greater anisotropy of white matter 53 . Even on a larger scale, this result seems to hold 61 .…”
Section: Tissue Considerationssupporting
confidence: 73%
“…For the bulk brain, typical elastic moduli reported range from a few 100 Pa to about 10 kPa in oscillatory shear rheological measurements in vitro, depending on strain, shear rate, preconditioning and several other factors 48 . This also holds for the spinal cord 48,53 and retina 54 . On a smaller scale, depending on the region of the CNS, different types, spatial orientations and relative numbers of neurons, glial cells and their processes, as well as different amounts of ECM, contribute to the mechanical properties measured 53,[55][56][57][58][59] .…”
Section: Tissue Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a), which is consistent with a role for mechanical gradients in helping to guide OT axons caudally 2 . In line with this idea, RGC axons from heterochronic eye primordia transplants growing throughXenopus brains at stages before the stiffness gradient is established grow rather straight and do not turn caudally in the mid-diencephalon 16 .We have previously shown that tissue stiffness scales with local cell body density 1,17 , and that in Xenopus embryo brains local stiffness gradients at later developmental stages (39/40) correlate with a gradient in cell density 2 . To determine if changes in cell densities are driving changes in tissue stiffness, and thus parallel the evolution of the stiffness gradient at earlier stages, we assayed cell densities using DAPI labelling of nuclei in whole-mounted brains with fluorescently labelled OTs, beginning at the morphological stage corresponding to the start of tiv-AFM measurements (33/34) and repeated for the two subsequent stages encompassing OT turning (35/36 and 37).…”
supporting
confidence: 52%
“…We have previously shown that tissue stiffness scales with local cell body density 1,17 , and that in Xenopus embryo brains local stiffness gradients at later developmental stages (39/40) correlate with a gradient in cell density 2 . To determine if changes in cell densities are driving changes in tissue stiffness, and thus parallel the evolution of the stiffness gradient at earlier stages, we assayed cell densities using DAPI labelling of nuclei in whole-mounted brains with fluorescently labelled OTs, beginning at the morphological stage corresponding to the start of tiv-AFM measurements (33/34) and repeated for the two subsequent stages encompassing OT turning (35/36 and 37).…”
mentioning
confidence: 99%